Miscellaneous Insect Pests of Florida Sugarcane - Gregg S. Nuessly; Ron H. Cherry; Hardev S. Sandhu; Julien M. Beuzelin (EDIS)
This 8-page fact sheet is a minor revision. The insects and mites discussed in this publication are occasional pests of sugarcane in Florida or are arthropods of concern although their pest status has not been determined. They have received less research interest and less is known about them, because they have not been as important as other sugarcane pests such as the corn wireworm (Melanotus communis) or the sugarcane borer (Diatraea saccharalis). However, these arthropods have the potential to become a problem if conditions favor an outbreak. Written by Gregg S. Nuessly, Ron H. Cherry, Hardev S. Sandhu, and Julien M. Beuzelin, and published by the Entomology and Nematology Department, July 2019.